Diagnosis and Treatment of Chronic Medical Conditions Among Trauma Patients at a Level 1 Trauma Center. Issue 10 (20th October 2020) - Amirhekmat, Arya; Dinicu, Andreea; Grimaud, Logan; Anderson, Amanda; Figueroa, Cesar; Smith, Megan; Barrios, Cristobal
Diabetes mellitus (DM) and hypertension (HTN) are increasing in prevalence in the population. Level 1 trauma facilities are often faced with managing these chronic conditions. Recent studies indicated that 12-44% of patients presenting traumas are found to have incidental findings by imaging representing undiagnosed medical conditions, with 10% reported requiring further management [Surendran A, Mori A, Varma DK, Gruen RL. Systematic review of the benefits and harms of whole-body computed tomography in the early management of multitrauma patients: Are we getting the whole picture? J Trauma and Acute Care Surg . 2014;76 (4):1122-1130]. Between 2015 and 2016, 852 patients seen at a level 1 trauma center were analyzed. Patients were evaluated who received a new diagnosis of HTN or DM, or had preexisting diagnosis of HTN or DM whose management was changed. Uncontrolled HTN or DM was defined as a need for either a change in medication or primary care optimization prior to discharge. Among the patients evaluated, 6.3% and 3.0% received new diagnoses of HTN and DM, respectively. Additionally, 34.4% and 35.3% of patients were found to have uncontrolled HTN and DM and required medical optimization, respectively. The high prevalence of undiagnosed or suboptimal management for chronic conditions indicates that more research is warranted for defining, screening for, and treating surgical patients with poorly controlled medical conditions with these comorbidities.